Food insecurity, chronic pain, and use of prescription opioids. (June 2021) - Men, Fei; Fischer, Benedikt; Urquia, Marcelo L.; Tarasuk, Valerie
Abstract: Chronic pain has been on the rise in recent decades in Canada. Accordingly, the use of prescription opioids (PO) in Canada increased drastically between 2005 and 2014, only starting to decrease in 2015. Both pain and PO use have serious public health repercussions, disproporionately affecting select socially disadvantaged populations. Food insecurity is a strong risk factor for mental disorders and suicidal outcomes, yet its relationship to chronic pain and PO use is largely unknown. Using two recent cycles from the population representative Canadian Community Health Survey (CCHS), we examined the association of household food insecurity status with chronic pain and PO use among Canadians 12 years and older, adjusting for health and sociodemographic characteristics. Compared to food-secure individuals, marginally, moderately, and severely food-insecure individuals had 1.31 (95% confidence interval [CI] 1.15–1.48), 1.89 (95% CI 1.71–2.08), and 3.29 (95% CI 2.90–3.74) times higher odds of experiencing chronic pain and 1.55 (95% CI 1.30–1.85), 1.77 (95% CI 1.54–2.04), and 2.65 (95% CI 2.27–3.09) times higher odds of using PO in the past year, respectively. The graded association with food insecurity severity was also found in severe pain experience and pain-induced activity limitations among chronic pain patients and, less consistently, in intensive, excess, and alternative use of PO and its acquisition through means other than medical prescription among past-year PO users. Food insecurity was a much more powerful predictor of chronic pain and PO use than other well-established social determinants of health like income and education. Policies reducing food insecurity may lower incidence of chronic pain and help contain the opioid crisis. Highlights: Food insecurity is associated with chronic pain and prescription opioids use. Food-insecure people's pain is more likely to be severe and cause activity limitation. Food insecurity predicts intensive, excess, and alternative use of prescription opioids. Food insecurity is a more powerful predictor of pain and prescription opioids use than income.